2014
DOI: 10.1097/tp.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Consequences of Injury and Repair in Older Organ Transplants

Abstract: Donor organ scarcity remains a significant clinical challenge in transplantation. Older organs, increasingly utilized to meet the growing demand for donor organs, have been linked to inferior transplant outcomes. Susceptibility to organ injury, reduced repair capacity, and increased immunogenicity are interrelated and impacted by physiological and pathological aging processes. Insights into the underlying mechanisms are needed to develop age-specific interventional strategies with regards to organ preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 158 publications
0
36
0
1
Order By: Relevance
“…The age of passenger leukocytes has previously been shown to impact allograft rejection 12-14 . However, age-related changes in parenchymal tissue may also be of relevance in allograft rejection 15-17 . Thus, to delineate whether the observed effects of donor age on allograft survival and systemic alloimmune responses were linked to age-dependent changes in parenchymal tissue or mediated by age-dependent modifications of passenger leukocytes residing within the graft, we generated chimeric C57BL/6 donor animals through lethal total body irradiation and subsequent hematopoietic reconstitution with bone marrow procured from young naïve syngeneic C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…The age of passenger leukocytes has previously been shown to impact allograft rejection 12-14 . However, age-related changes in parenchymal tissue may also be of relevance in allograft rejection 15-17 . Thus, to delineate whether the observed effects of donor age on allograft survival and systemic alloimmune responses were linked to age-dependent changes in parenchymal tissue or mediated by age-dependent modifications of passenger leukocytes residing within the graft, we generated chimeric C57BL/6 donor animals through lethal total body irradiation and subsequent hematopoietic reconstitution with bone marrow procured from young naïve syngeneic C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the subanalysis of donors aged ≥50 years, the use of the HP did not reduce the DGF rate, but the duration of DGF was lower than in the control group, which might have a positive impact in long‐term results. The lack of benefits with related to the use of MP after a long CIT in transplants from expanded criteria donors may be due to these kidneys are more susceptible to ischemic injury in general, they have lower renal mass, more chronic histologic injuries, and lower ability for repair and regeneration . However, we must consider that these subanalysis involved a small sample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As transplantations with organs from donors aged ≥50 years and transplants from expanded criteria donors are associated with worse outcomes after transplantation, such as higher rates of DGF and lower graft survival, 23 we performed a subanalysis considering only donors aged ≥50 years and expanded criteria donors. A subanalysis including only expanded criteria donors showed that the use of HP did not improve results after the transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, on unifactorial analysis, patients who were paced were significantly more likely to have had a donor‐to‐recipient weight ratio >2.0 in comparison with those who were not paced. Extreme size mismatch has been shown to increase the risk of primary graft failure, possibly due to longer operative and ischemic times associated with a difficult implant procedure …”
Section: Discussionmentioning
confidence: 99%